2020
DOI: 10.1161/jaha.119.015625
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Diagnostic Evaluation in Women and Men After Acute Ischemic Stroke

Abstract: Background Sex differences have been found in stroke risk factors, incidence, treatment, and outcomes. There are conflicting data on whether diagnostic evaluation for stroke may differ between men and women. Methods and Results We performed a retrospective cohort study using inpatient and outpatient claims between 2008 and 2016 from a nationally representative 5% sample of Medicare beneficiaries. We included patients ≥65 years old and hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
2
10
0
1
Order By: Relevance
“…Consistent with a recent study [23], the only disparity we found by sex was lower CTA utilization in female patients. Although a sex-based neuroimaging disparity was not found by others [22], this finding, along with less CTA utilization in patients with diabetes mellitus, renal insufficiency, and age !…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with a recent study [23], the only disparity we found by sex was lower CTA utilization in female patients. Although a sex-based neuroimaging disparity was not found by others [22], this finding, along with less CTA utilization in patients with diabetes mellitus, renal insufficiency, and age !…”
Section: Discussionsupporting
confidence: 92%
“…In the hospital setting, socioeconomic disparities exist for patients with stroke in terms of access to treatment [11,15,16]. Additionally, variability in stroke imaging utilization on the basis of age, sex, race, and insurance type has been reported [12,[22][23][24][25]. Furthermore, disadvantaged socioeconomic groups have historically been the last to benefit from newer medical technologies [26].…”
Section: Introductionmentioning
confidence: 99%
“…AIS patients were identified using the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) diagnosis codes (433.01, 433.11, 433.21, 433.31, 433.81, 433.91, 434.01, 434.11, 434.91, and 436) and International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) diagnosis codes (I21). 18 These codes have a specificity of 95% and positive predictive value of 90% for AIS. 19 The NRD variable "DISPUNIFORM" was used to identify DAMA.…”
Section: Study Populationmentioning
confidence: 99%
“…19,20 Diagnostic workup: Women with AIS symptoms are less likely to see a stroke specialist and to undergo standard diagnostic testing than men. 21,22 Vascular imaging is performed less often in women. 22 Intravenous thrombolysis: Women are 13% less likely to receive intravenous thrombolysis than men in Western countries.…”
Section: Baseline Statusmentioning
confidence: 99%
“…21,22 Vascular imaging is performed less often in women. 22 Intravenous thrombolysis: Women are 13% less likely to receive intravenous thrombolysis than men in Western countries. 18 Underuse and delay in intravenous thrombolysis in women are more pronounced in hospitals without specialized stroke unit care.…”
Section: Baseline Statusmentioning
confidence: 99%